Evaluation of CpG DNA for Increasing Immune Gene Expression in Grouper (Epinephelus fuscoguttatus) - Jamaluddin, Ruqayyah; Yusuf, Sunarti; Nursida, Nur Fajriani; Suryahman, Agus; Tahya, Akbar Marzuki (FAPETKAN UNTAD, 2020)
CpG DNA is a kind of DNA synthetic immunostimulant containing CpG motifs consisting of short sequences containing one or more CpG motifs which act as a danger signal to the natural and innate immune systems. This study aimed to analyze the ability of CpG DNA to increase Interleukin 1Î² (IL1Î²) gene expression in tiger grouper so that it could be used as immunostimulant. Analysis of the expression level was carried out by extracting RNA- from the cephalic kidney which was treated with CpG DNA or with PBS as a control. Complementary DNA (cDNA) synthesis was carried out using the Ready To Go You Prime First Strand Beads (GE Healthcare) kit using the RT-PCR technique. The PCR product was analized by measuring the photostimulated luminescence value using UN SCAN IT software based on the thickness of the DNA fragments. The gene expression level and photostimulated luminescence value of the IL1Î² gene were higher than that of the PBS treatment used as a control. The luminescence value of the photostimulated IL1Î² gene in CpG DNA treatment was 113684 while the PBS treatment as a control was only 95610.